2015
DOI: 10.1371/journal.pone.0123229
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Functions and Stereopsis in Patients with Parkinson’s Disease and Alzheimer’s Disease Using 3-Dimensional Television: A Case Controlled Trial

Abstract: Stereopsis or depth perception is an awareness of the distances of objects from the observer, and binocular disparity is a necessary component of recognizing objects through stereopsis. In the past studies, patients with neurodegenerative disease (Alzheimer dementia, AD; Parkinson’s disease IPD) have problems of stereopsis but they did not have actual stimulation of stereopsis. Therefore in this study, we used a 3-dimensional (3D) movie on 3D television (TV) for actual stereopsis stimulation. We propose resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 50 publications
0
28
0
Order By: Relevance
“…Deficits in motion perception have been associated with severity of dementia, and evidence suggests that AD patients may have impaired motion sensitivity due to selective damage to the magnocellular pathway [31, 65, 83, 99]. Although reduced depth perception and stereopsis have been linked with cognitive impairment, opinions regarding the effect of stereopsis in AD patients are mixed [31, 115, 158]. Finally, saccadic eye movement is among the most well-described deficits to ocular motor function in AD patients [36, 53].…”
Section: Visual Dysfunction In Ad Patients and Animal Modelsmentioning
confidence: 99%
“…Deficits in motion perception have been associated with severity of dementia, and evidence suggests that AD patients may have impaired motion sensitivity due to selective damage to the magnocellular pathway [31, 65, 83, 99]. Although reduced depth perception and stereopsis have been linked with cognitive impairment, opinions regarding the effect of stereopsis in AD patients are mixed [31, 115, 158]. Finally, saccadic eye movement is among the most well-described deficits to ocular motor function in AD patients [36, 53].…”
Section: Visual Dysfunction In Ad Patients and Animal Modelsmentioning
confidence: 99%
“…Stereopsis is the perception of depth and 3D structure obtained from binocular vision. Studies have shown that patients with AD have reduced stereopsis as compared to control groups, and some also note a correlation between cognitive assessment scores and performance on stereopsis testing ( 59 , 60 ).…”
Section: Visual Manifestations Of Admentioning
confidence: 99%
“…Some limited research on neurodegenerative diseases such as Parkinson's disease, schizophrenia, and multiple sclerosis have reported deterioration of stereopsis in these patients. [20][21][22][23] Stereopsis in patients with DM has not been previously investigated at any stages of DR. Since strong evidence exists for neurodegeneration in early stages of diabetic retinopathy, 12 we speculate that some functional changes in depth perception may also be present at this stage.…”
Section: Introductionmentioning
confidence: 99%